Death of a Son is Associated With Risk of Suicide Among Parous Women in Taiwan: A Nested Case-Control Study - Chen, Chih-Cheng (Japan Epidemiological Association, 2012)
BACKGROUND: The impact of the sex of a deceased child on maternal suicide has not been studied. We examined whether the death of a child, especially a son, increased the risk of suicide among parous Taiwanese women. METHODS: This matched case-control study was done within a cohort of 1 292 462 Taiwanese women who experienced a first and singleton childbirth between 1 January 1978 and 31 December 1987 and were followed up until 31 December 2008. From the cohort, 2701 suicide cases were identified and 2701 controls were randomly selected. Multiple logistic regression was used to estimate the risk of suicide associated with the death of a child. RESULTS: The adjusted odds ratios (ORs) for suicide among mothers whose son had died were 2.60 (95% CI = 1.18–5.73), 2.58 (1.28–5.20), and 4.20 (0.79–22.45) for death of a son aged younger than 1 year, 1 to 17 years, and 18 years or older. The ORs for suicide associated with the death of a daughter were not statistically significant: the respective adjusted ORs were 1.86 (0.82–4.62), 1.38 (0.54–3.49), and 2.48 (0.40–15.51). CONCLUSIONS: The death of a child, especially a son, increased the risk of maternal suicide, which supports the notion that preference for a son is firmly rooted in traditional Chinese culture.